Sensor-based behavioral patterns can identify heat-sensitive lactating dairy cows - G. Ranzato; I. Lora; B. Aernouts; I. Adriaens; F. Gottardo; G. Cozzi (International Journal of Biometeorology, 2023)
Heat stress impairs the health and performance of dairy cows, yet only a few studies have investigated the diversity of cattle behavioral responses to heat waves. This research was conducted on an Italian Holstein dairy farm equipped with precision livestock farming sensors to assess potential different behavioral patterns of the animals. Three heat waves, defined as at least five consecutive days with mean daily temperature-humidity index higher than 72, were recorded in the farm area during the summer of 2021. Individual daily milk yield data of 102 cows were used to identify “heat-sensitive” animals, meaning the cows that, under a given heat wave, experienced a milk yield drop that was not linked with other health events (e.g., mastitis). Milk yield drops were detected as perturbations of the lactation curve estimated by iteratively using Wood’s equation. Individual daily minutes of lying, chewing, and activity were retrieved from ear-tag-based accelerometer sensors. Semi-parametric generalized estimating equations models were used to assess behavioral deviations of heat-sensitive cows from the herd means under heat stress conditions. Heat waves were associated with an overall increase in the herd’s chewing and activity times, along with an overall decrease of lying time. Heat-sensitive cows spent approximately 15 min/days more chewing and performing activities ( p < 0.05). The findings of this research suggest that the information provided by high-frequency sensor data could assist farmers in identifying cows for which personalized interventions to alleviate heat stress are needed.

Macronutrient biogeochemistry in Antarctic land-fast sea ice: Insights from a circumpolar data compilation - Sian F. Henley; Stefano Cozzi; François Fripiat; Delphine Lannuzel; Daiki Nomura; David N. Thomas; Klaus M. Meiners; Martin Vancoppenolle; Kevin Arrigo; Jacqueline Stefels; Maria van Leeuwe; Sebastien Moreau; et al. (Marine Chemistry, 2023)

Fungal isolates and metabolites in locally processed rice from five agro-ecological zones of Nigeria - Rofiat Abdus-Salaam; Olusegun Atanda; Francesca Fanelli; Micheal Sulyok; Giuseppe Cozzi; Simona Bavaro; Rudolf Krska; Antonio F. Logrieco; Chibundu N. Ezekiel; Waheed A. Salami (Food Additives & Contaminants Part B-Surveillance, 2016)

Fungal and bacterial metabolites associated with natural contamination of locally processed rice ( Oryza sativa L.) in Nigeria - Abdus-Salaam Rofiat; Francesca Fanelli; Olusegun Atanda; Michael Sulyok; Giuseppe Cozzi; Simona Bavaro; Rudolf Krska; Antonio F. Logrieco; Chibundu N. Ezekiel (Food Additives & Contaminants: Part A, 2015)

Density and habitat use of lions and spotted hyenas in northern Botswana and the influence of survey and ecological variables on call-in survey estimation - G. Cozzi; F. Broekhuis; J. W. McNutt; B. Schmid (Biodiversity and Conservation, 2013)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Climate-related variations in crustal trace elements in Dome C (East Antarctica) ice during the past 672 kyr - Alexandrine Marteel; Vania Gaspari; Claude F. Boutron; Carlo Barbante; Paolo Gabrielli; Paolo Cescon; Giulio Cozzi; Christophe P. Ferrari; Aurélien Dommergue; Kevin Rosman; Sungmin Hong; Soon Do Hur (Climatic Change, 2009)

Distinct Na+/K+/2Cl- cotransporter localization in kidneys and gills of two euryhaline species, rainbow trout and killifish - Fumi Katoh; Regina R. F. Cozzi; William S. Marshall; Greg G. Goss (Cell and Tissue Research, 2008)

Behavioural modifications of bitches during diestrus and anestrus - A. Gazzano; A. Cozzi; C. Mariti; L. Tidu; E. Verri; M. Ducci; F. Martelli (Veterinary Research Communications, 2008)

Is PM10 mass measurement a reliable index for air quality assessment? An environmental study in a geographical area of north-eastern Italy - F. Cozzi; G. Adami; P. Barbieri; E. Reisenhofer; M. Bovenzi (Environmental Monitoring and Assessment, 2008)

Effect of Plant Maturity and Germplasm on in situ Rumen Degradability and Rate of Passage of Alfalfa Hay - M. Dorigo; F. Gottardo; P. Berzaghi; G. Cozzi (Veterinary Research Communications, 2005)

Characterization of INTA 51-3, a New Atypical Strain of Bacillus thuringiensis from Argentina - Graciela B. Benintende; Joel E. López-Meza; Jorge G. Cozzi; Carlos F. Piccinetti; Jorge E. Ibarra (Current Microbiology, 2000)

Hydrogeochemical Precursors in Kamchatka (Russia) Related to the Strongest Earthquakes in 1988–1997 - P. F. Biagi; A. Ermini; E. Cozzi; Y. M. Khatkevich; E. I. Gordeev (Natural Hazards, 2000)

Short-Term Changes of Response Indicators of Ecosystem Status in Broadleaved Forests in Tuscany (Central Italy) - M. Ferretti; I. Bonini; F. Bussotti; C. Celesti; E. Cenni; A. Chiarucci; A. Cozzi; V. De Dominicis; P. Grossoni; C. Leonzio (Water, Air, & Soil Pollution, 1999)

Implementation of Quality Assurance Procedures in the Italian Programs of Forest Condition Monitoring - M. Ferretti; F. Bussotti; E. Cenni; A. Cozzi (Water, Air, & Soil Pollution, 1999)

Aquifer-induced Seismicity in the Central Apennines (Italy) - F. Bella; P. F. Biagi; M. Caputo; E. Cozzi; G. Della Monica; A. Ermini; W. Plastino; V. Sgrigna (Pure and Applied Geophysics, 1998)